Use of calcium and boron in the production of grain and sunflower silage - Thomas Newton Martin; Paulo Sergio Pavinato; Luis Fernando Glassenap de Menezes; Luis Antônio Santi; Patricia Bertoncelli; Sidney Ortiz (Semina: Ciências Agrárias, 2014)
Boron and calcium are related to many physiological processes of the plant, which are affected by its deficiency, such as sugar transport, synthesis and cell wall structure, carbohydrate metabolism and plasma membrane integrity. The objective of this study was to evaluate the efficiency of boron and calcium application via leaf and soil on the yield components in silage quality and content of macronutrients in leaves of sunflower. The experiment was conducted at Universidade Tecnológica Federal do Paraná – UTFPR, Campus Dois Vizinhos, from September 2008 to April 2009, in a randomized block design with four replications, using the genotype Agrobel - La Tijereta. Morphological characteristics of the plants, the yield components (grain yield and weight of hundred grains), silage quality and content of nutrient uptake were evaluated. The sunflower crop did not respond to application of boron and calcium, to effects on yield components in silage quality and content of nutrients absorbed by plants. However, it was found increases in the partition dry grain and plant height.